Effect of different packaging material on storage and quality attributes of kiwi fruits (Actinidia deliciosa Planch) - Chettri, Kush; Upadhyay, Sujata; Bhutia, Karma Diki; Sharma , Laxuman (Journal of Postharvest Technology, 2022)
The present study was undertaken at the Dept. of Horticulture, Sikkim University, Gangtok during 2019-2020 to assess the effect of different packaging materials on storage and quality attributes of kiwi fruit (Actinidia deliciosa Planch) cv. Monty. After harvesting the fruits, they were packed under different packaging conditions, i.e. six treatments: control (open condition), LDPE, LDPE (perforated), Brown paper, Brown Paper (perforated), and vacuum packaging at room temperature with three replications. The statistical analysis was done using a Completely Randomised Design (CRD). The biochemical parameters, e.g. physiological loss in weight, moisture (%), T.S.S., titratable acidity (%), reducing sugar (%), total sugar (%), were also studied. The sensory evaluation was also done. The lowest PLW (physiological loss in weight) was recorded in T2 (LDPE perforated) and T0 (control), followed by T4 (brown paper perforated) and T5 (vacuum packaging). The maximum average value of TSS (14.510 Bx) was observed on the 25th day. Also, the highest average TSS was observed in T2 (LDPE perforated) (12.350 Bx), followed by T4 (Brown paper perforated) (11.870 Bx). The maximum titratable acidity content was observed in T1 (LDPE) (1.49%), followed by T4 (brown paper perforated) (1.39%). The maximum ascorbic acid content was observed in T2 (LDPE perforated) (80.83 mg/100g) and T4 (brown paper perforated) (79.38%). The maximum reducing sugar content was found in T5 (vacuum packaging) (7.44%), and T4 (brown paper perforated) (7.22%). The highest sugar value was recorded in T3 (brown paper) (9.9%) and T5 (vacuum packaging) (9.42%). The highest percentage of moisture content was recorded in T2 (LDPE perforated) (70.41%) and T3 (Brown paper) (70.38%) respectively. Fruits which were packed in T4 (Brown paper perforated) (7.01) had the highest sensory scoring, followed by T2 (LDPE perforated) (6.86). From the present study, it was revealed that the kiwi fruits kept under different packaging conditions under room temperature can survive up to 30 days after harvesting. Fruits which were kept under brown paper perforated and LDPE perforated extended the shelf life of kiwifruit for the longest duration with the best marketing and edible quality.